Ecological study of carrots of the canteen selection of the Federal scientific vegetable center in the conditions of the south of the Rostov region - L. A. Yusupova; A. N. Khovrin; O. V. Kotlyarova (Овощи России)
The results of ecological variety testing of table carrot samples in soil and climatic conditions of the south of the Rostov region are presented. The experiments were laid in the period 2020 and 2021 in the fields of the Biryuchekut OSOS branch of the FSBI FNCO in the city of Novocherkassk, Rostov region. 12 samples of carrot plants from the first year of life were studied. The most productive samples were Marlinka – 59.7 t/ha Aksinya – 55.3 t/ha and Abaco F1 standard – 51.9 t/ha. The marketability of root crops was higher in the samples of Shantane 2461-82%, Aksinya – 78.9%, Boyar – 74.2% and Primorskaya 22-72.9%. The conducted research makes a great contribution to the process of selecting the source material for the creation of new varieties and hybrids of table carrots. The isolated samples can be recommended for commercial cultivation in the Rostov region and used in breeding work as a starting material.